Design and pilot validation of A-gear: a novel wearable dynamic arm support. Issue 1 (December 2015) - Kooren, Peter; Dunning, Alje; Janssen, Mariska; Lobo-Prat, Joan; Koopman, Bart; Paalman, Micha; de Groot, Imelda; Herder, Just
Abstract Background Persons suffering from progressive muscular weakness, like those with Duchenne muscular dystrophy (DMD), gradually lose the ability to stand, walk and to use their arms. This hinders them from performing daily activities, social participation and being independent. Wheelchairs are used to overcome the loss of walking. However, there are currently few efficient functional substitutes to support the arms. Arm supports or robotic arms can be mounted to wheelchairs to aid in arm motion, but they are quite visible (stigmatizing), and limited in their possibilities due to their fixation to the wheelchair. The users prefer inconspicuous arm supports that are comfortable to wear and easy to control. Methods In this paper the design, characterization, and pilot validation of a passive arm support prototype, which is worn on the body, is presented. The A-gear runs along the body from the contact surface between seat and upper legs via torso and upper arm to the forearm. Freedom of motion is accomplished by mechanical joints, which are nearly aligned with the human joints. The system compensates for the arm weight, using elastic bands for static balance, in every position of the arm. As opposed to existing devices, the proposed kinematic structure allows trunk motion and requires fewer links and less joint space without compromising balancing precision. The functional prototype has been validated in three DMD patients, using 3D motion analysis. Results Measurements have shown increased arm performance when the subjects were wearing the prototype. Upward and forward movements were easier to perform. The arm support is easy to put on and remove. Moreover, the device felt comfortable for the subjects. However, downward movements were more difficult, and the patients would prefer the device to be even more inconspicuous. Conclusion The A-gear prototype is a step towards inconspicuousness and therefore well-received dynamic arm supports for people with muscular weakness.